Thomas Erastus and the Palatinate : a Renaissance physician in the Second Reformation - Gunnoe, Charles D., 1963- (Brill's series in church history ;, 2011)
This study is the first monograph to attempt a synthetic treatment of the career of Thomas Erastus (1524-1583). Erastus was a central player in the conversion of the Electoral Palatinate to Reformed Christianity in the early 1560s and a co-author of the Heidelberg Catechism. In the church discipline controversy of the 1560s and 1570s, Erastus opposed the Calvinist effort to institute a consistory of elders with independent authority over excommunication. Erastus's defeat in this controversy, and the ensuing Antitrinitarian affair, proved the watershed of his career. He turned to the refutation.